Charm-Quark Contribution to K_L -> mu^+ mu^- at Next-to-Next-to-Leading - Gorbahn, M; Haisch, U (2006)
We calculate the charm-quark contribution to the decay K_L -> mu^+ mu^- in next-to-next-to-leading order of QCD. This new contribution reduces the theoretical uncertainty in the relevant parameter P_c from +/-22% down to +/-7%, corresponding to scale uncertainties of +/-3% and +/-6% in the short-distance part of the branching ratio and the determination of the Wolfenstein parameter rhobar from K_L -> mu^+ mu^-. The error in P_c = 0.115 +/- 0.018 is now in equal shares due to the combined scale uncertainties and the current uncertainty in the charm-quark mass. We find BR (K_L -> mu^+ mu^-)_SD = (0.79 +/- 0.12) x 10^-9, with the present uncertainty in the Cabibbo-Kobayashi-Maskawa matrix element V_td being the dominant individual source in the quoted error.